Meningkatkan kebugaran fisik melalui gamifikasi: Bukti dari siswa sekolah menengah kejuruan - Purwanto, Didik; Gunawan, Gunawan; Kamarudin, Kamarudin (Universitas Nusantara PGRI Kediri, 2025)
Physical fitness is an essential component for vocational high school (SMK) students, as it directly relates to their productivity and readiness for future work demands. This study aimed to examine the effect of gamification-based Physical Education on the physical fitness of vocational high school students in Palu, South Sulawesi. A quasi-experimental non-equivalent control group design was employed with a sample of 30 students divided into two groups: an experimental group (physical education learning with gamification) and a control group (conventional physical education learning). Standardized physical fitness tests—including flexibility, muscular strength, endurance, and BMI—were administered before and after the intervention. Results showed that the experimental group’s average score increased from 2.73 (pre-test) to 4.60 (post-test), while the control group improved from 2.67 to 4.20. Paired sample t-tests confirmed significant improvements within both groups (p < 0.05). However, the independent sample t-test indicated no significant difference between the experimental and control groups (p = 0.077 > 0.05). These findings suggest that gamification can effectively enhance students’ physical fitness within a group, but its short-term implementation does not demonstrate superiority over conventional methods. This study contributes to the growing body of literature on innovative approaches in physical education, particularly in vocational schools, where physical readiness is closely linked to employability. Gamification shows potential as a complementary strategy to boost student motivation and engagement in physical education. Future research is recommended with longer intervention periods, larger samples, and consideration of external variables to optimize the impact of gamification on physical fitness.